1992
DOI: 10.1007/bf00318700
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the peri-insular extracellular matrix for islet isolation from the pancreas of rat, dog, pig, and man

Abstract: The presence and distribution in the peri-insular region of extracellular matrix, and in particular basement membrane, was investigated in a comparative study comprising pancreata of rat, dog, pig, and man. Basement membrane markers, collagen type-IV and laminin, were determined immunohistochemically. Additional information pertaining to the structural relationships between endocrine and exocrine pancreas, in particular cell-to-cell and cell-to-matrix contacts, was obtained by electron microscopy. In pig, very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(87 citation statements)
references
References 30 publications
3
82
0
2
Order By: Relevance
“…Our results show that major ECM proteins are absent extracellularly between islet cells, as are nidogen-1 and fibulin-1 and -2. Similarly, a range of collagen isoforms-fibronectin, vitronectin, and elastin-were not detected between islet cells (van Deijnen et al 1992;Meyer et al 1997). These studies provide molecular evidence to support a previous electron microscopic study (Like et al 1978) that a BM structure is not found around islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that major ECM proteins are absent extracellularly between islet cells, as are nidogen-1 and fibulin-1 and -2. Similarly, a range of collagen isoforms-fibronectin, vitronectin, and elastin-were not detected between islet cells (van Deijnen et al 1992;Meyer et al 1997). These studies provide molecular evidence to support a previous electron microscopic study (Like et al 1978) that a BM structure is not found around islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings have indicated that in the human pancreas, endocrine cells are separated from exocrine cells by reticulin fibres [15] and the endocrine-exocrine interface in different species variably appears to contain collagens I, IV, V and VI, as well as Lm [16][17][18]. Electron microscopy detected [19] a typical BM facing the endocrine cell at the endocrine-exocrine interface as a peri-islet BM, but the same study failed to detect BM inside human islets. Recent studies have provided evidence of the unique cytoarchitecture of human pancreatic islets when compared with that of rodents [20,21].…”
Section: Introductionmentioning
confidence: 96%
“…Unfortunately, despite many reports on the isolation of adult porcine islets, factors such as age, breed, and quality of organs adversely affect the final yield (18,19), and, once isolated, adult porcine islets are fragile and difficult to maintain in tissue culture (17,20,21). The fragility of these islets significantly decreases yields of islet cells particularly when culture procedures are used to reduce graft immunogenicity or when low temperature storage is used to combine isolates from multiple donors.…”
Section: Introductionmentioning
confidence: 99%